2008
DOI: 10.1111/j.1460-9592.2008.02530.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of head posture on the oral, pharyngeal and laryngeal axis alignment in infants and young children by magnetic resonance imaging

Abstract: In infants and young children, under general anesthesia and with a laryngeal mask airway in place, just a slight head extension improves alignment of the line of vision of the glottis and the laryngeal axis (narrowing of angle delta) but worsened the alignment of the pharyngeal and laryngeal axes (widening of angle beta).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…The optimal position of the head to maintain airway patency in children has been frequently investigated. Based on MRI, Vialet et al (6) in 2008 showed that slight extension of the head in infants and young children was optimal in improving the alignment of the axes of the airway. Hence, the choice of the control group was aiming to provide children with the maximal expected airway patency without application of the neck collar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal position of the head to maintain airway patency in children has been frequently investigated. Based on MRI, Vialet et al (6) in 2008 showed that slight extension of the head in infants and young children was optimal in improving the alignment of the axes of the airway. Hence, the choice of the control group was aiming to provide children with the maximal expected airway patency without application of the neck collar.…”
Section: Discussionmentioning
confidence: 99%
“…Head extension may be an important component maintaining airway patency. One should keep in mind that with loss of consciousness, the head moves spontaneously in flexion hence obstructing the airway . Taken together, these data suggest that a device such as a neck support collar designed to prevent downward displacement of the mandible as well as maintaining the head in slight extension during sleep may be beneficial in maintaining patency of the airway during pediatric sedation.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 For this reason, the sniffing position, which is the alignment of the external auditory meatus (EAM) and sternal notch in the horizontal plane, is recommended to achieve an optimal laryngeal view. 14,[16][17][18] However, a comparison of the use of this simple procedure to align the sternal notch and EAM with other forms of laryngoscopy has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…An important advantage of MRI for imaging of the pediatric larynx is the limited need for anesthetics. However, many of the earlier studies on MR imaging of the pediatric larynx had the primary aim to visualize the effects of anesthesia and deep sedation on the airway . A reported side effect of anesthetics is respiratory distress, which in children is mainly caused by apnoea and upper airway collapse .…”
Section: Resultsmentioning
confidence: 99%
“…Litman et al, Vialet et al, and Bécret et al further investigated the sedated laryngeal dimensions, concluding that the collapse of the pediatric airway during sedation can be partly overcome by positioning the child in either lateral or neutral position with a slight head extension …”
Section: Resultsmentioning
confidence: 99%